Pengaruh Return On Equity, Rapat Direksi, dan Umur Perusahaan Terhadap Management Discussion & Analysis - Sudrajat, Ajat; Umdiana, Nana (Akuisisi : Jurnal Akuntansi, 2024)
The purpose of this study is to prove the effect of return on equity, board of directors meeting, and firm age on the extent of disclosure in management discussion and analysis. The object of this research is a listed manufacturing company in Indonesia Stock Exchange from 2018-2022. The sampling technique used purposive sampling method which obtained a sample of 600 units of analysis. The analysis technique in this study uses multiple linear regression analysis to prove that return on equity, board of directors meeting, and firm age has an effect on management discussion and analysis. The result of this study shows that return on equity, board of directors meeting, and firm age has an effect on management discussion and analysis. Companies with low levels of disclosure in their management discussion and analysis reports are encouraged to pay more serious attention, particularly those that have been established for a long time. Additionally, it is important to focus on improving financial performance and increasing the frequency of board meetings to ensure that the information provided to external users is of higher quality